The role of ultrasound in diagnosing 2mm medullary thyroid carcinoma with cervical lymph node metastasis: a case report - Wan, Qinyun; Sun, Li; Gan, Lu; Liu, Jianxue (Frontiers in Oncology, 2025)
BackgroundMedullary thyroid carcinoma (MTC) is a rare, aggressive thyroid cancer, comprising 5%-10% of cases, often leading to cervical lymph node metastasis.Case presentationWe report a 49-year-old woman with a 2 mm micro-nodule in the left thyroid lobe and two suspicious lymph nodes in the neck. Ultrasound-guided fine needle aspiration indicated MTC, confirmed by immunohistochemical analysis. Following total thyroidectomy and left cervical lymphadenectomy, two of 26 lymph nodes showed metastasis. The cancer was 2 mm, with no capsular invasion, and positive markers for MTC were noted. This case emphasizes the importance of early MTC detection in micro-nodules and thorough lymph node evaluation.ConclusionEven a 2 mm MTC has the potential to metastasize lateral cervical lymph nodes. This emphasizes the necessity of meticulous ultrasound evaluation by experienced clinicians to detect abnormal lymph nodes and inform clinical management. Interventional ultrasound plays a crucial role in both diagnosing MTC micro-nodules and identifying associated lymph node metastases.